Basic thermodynamics - Carrington, Gerald (Oxford science publications, 1994)
It is well known that thermodynamics presents students with particular difficulties. They find the concepts evasive and the methods obscure. These problems arise because it is traditional to emphasize at the outset how general thermodynamics is. Unfortunately, when ideas are introduced in an unspecific context they fail to make contact with the student's experience - such ideas do not become part of the physical intuition of the student. In this introductory text the subject is developed in stages beginning with the basic notions, which are illustrated using an ideal gas as a model system. The generalization of these concepts is achieved first using the classical laws of thermodynamics and second using the formalism of Gibbs to provide a systematic introduction to the thermodynamic potentials. Work processes on polarizable media subject to electric and magnetic fields are discussed and transformations of matter, including phase change processes and chemical reactions, are treated in detail. The book contains many worked examples, and approximately 250 questions, which are keyed to the text. The questions include traditional and applied topics, and longer questions have been programmed to guide the student.